Firsakova, Slava Konstantinovna (director of the Gomel' research institute of agricultural radioecology)
About national sanitary standards; the safety of nuclear energy; the rehabilitation of natural resources in Belarus; major dangers of Chernobyl are in the past; about the evacuation program as an exaggeration; need to combat Chernobyl psychologically; criticism of 'alarmists' scientists.